Early refractive outcome after intravitreous bevacizumab for retinopathy of prematurity - Harder, Björn; Baltz, Stefan von; Schlichtenbrede, Frank; Jonas, Jost B. (Archives of ophthalmology, 2012)
Retinopathy of prematurity (ROP) is a neovascular retinal disease that has usually been treated by peripheral argon laser coagulation. Retinal laser coagulation has disadvantages and adverse effects such as the need for general anesthesia, scarring of the peripheral retina and choroid, and...